MAGE: a distributed programming model - Barr, E.; Pandey, R.; Huangs, M. (21st International Conference on Distributed Computing Systems (ICDCS 2001), 2001)
Writing distributed programs is difficult. To ease this task, we introduce a new programming abstraction which we call a mobility attribute. Mobility attributes provide a syntax that describes the mobility semantics of program components. Programmers attach mobility attributes to program components to dynamically control the placement of these components within the network. Mobility attributes intercept component invocations and decide whether and where to move a component before the component executes. This allows the programmer to improve her program's runtime efficiency by colocating components and resources. We present MAGE, an object oriented distributed system, that supports mobility attributes and illustrates their utility.